Improving elements of haricot bean value chain in Alaba Special District, Southern Ethiopia: Experiences from IPMS - Shiferaw, A.; Berhe, Kahsay; Jaleta, Moti; Gebremedhin, Berhanu; Hoekstra, Dirk (International Livestock Research Institute, 2010)
The Improving Productivity and Market Success (IPMS) of Ethiopian Farmers project adopted a “participatory market oriented commodity value chain development” approach, to address problems and potentials for haricot bean production in Alaba Special District, in Southern Ethiopia. With an emerging export market potential, attention needs to be paid not only to the production of haricot beans but also to the supply of inputs and services and marketing. Major problems diagnosed by the value chain partners included poor access to inputs including seeds, weed and disease problems, poor technology adoption and marketing of haricot bean. To address the above problems, various development actors developed haricot bean commodity with the IPMS project and Alaba Special District Office of Agriculture and Rural Development (OoARD) introduced value chain interventions for the past five years (2005 to 2010). Initial intervention focused at building farmers capacity to multiply seed and establish seed bank using visits, trainings, demonstration, workshops, promotion and discussion. Later, to improve supply of inputs (seeds, fertilizer and agro-chemicals) support was provided to establish cooperative shop, private crop protection service and revolving fund with IPMS credit fund while comparing soil fertility technologies. Additional effort also focused at marketing of small pack, promotion of haricot bean, market linkage and establishment of seed cooperative. Findings show an increase in farmers’ market participation from 54.5% in 2004 during baseline survey to 92% in 2009 during sample household survey. There is an increase in the proportion of farmers’ producing seed and change in focus from household consumption to seed business in targeted 19 PAs (Peasant Association). Survey results show a higher yield (9.5qt/ha) among fertilizer users compared with non users (7.2 qt/ha). On-farm yield plot trial (n=387) with 129 households (HH) in 17 PAs for three years shows mean yield of 7.04, 4.1 and 2.76 qt/ha for chemical fertilizer, haricot bean inoculants and control plots respectively. Farmers have clearly indicated their preference for the red and/or speckled varieties to white varieties. Increase in haricot bean seed multipliers from 64 HH in 4 PA to 426 HH in 19 PAs resulted in establishment of seed cooperative. While more actors are increasingly involved in value chain development leading to market oriented production, there is informal partnership and poor linkage among value chain actors. The study draws lessons on increasing production of haricot bean, strengthening input supply system and development of market intervention. On the basis of the findings, the paper outlines challenges, lessons and provides recommendations to improve existing value chain for development partners.